2018
DOI: 10.3390/bioengineering5030059
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional (3D) Printed Microneedles for Microencapsulated Cell Extrusion

Abstract: Cell-hydrogel based therapies offer great promise for wound healing. The specific aim of this study was to assess the viability of human hepatocellular carcinoma (HepG2) cells immobilized in atomized alginate capsules (3.5% (w/v) alginate, d = 225 µm ± 24.5 µm) post-extrusion through a three-dimensional (3D) printed methacrylate-based custom hollow microneedle assembly (circular array of 13 conical frusta) fabricated using stereolithography. With a jetting reliability of 80%, the solvent-sterilized device with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 141 publications
(176 reference statements)
0
46
0
Order By: Relevance
“…Some reports use a syringe system and different concentrations of the sodium alginate solution for microcapsule crosslinking. The diameter of the capsules produced in these studies can range from 10 to 1000 µm [ 42 , 43 , 44 , 45 ]. However, a complete device is described herein, so that groups wishing to work with cellular microencapsulation can produce their own low-cost equipment, with reproducible results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports use a syringe system and different concentrations of the sodium alginate solution for microcapsule crosslinking. The diameter of the capsules produced in these studies can range from 10 to 1000 µm [ 42 , 43 , 44 , 45 ]. However, a complete device is described herein, so that groups wishing to work with cellular microencapsulation can produce their own low-cost equipment, with reproducible results.…”
Section: Discussionmentioning
confidence: 99%
“…Chantel Farias and collaborators used a microencapsulation system with parameters similar to ours to microencapsulate HepG2 cell and human glioblastoma cell (U-87) in 2018. The authors observed significant loss of viability post-24 h incubation of the microencapsulated HepG2 cells, probably due to the spheroid formation detected after a day, limiting diffusion transport of oxygen and nutrients due to a stagnant microenvironment [ 43 ]. In our system, we have shown that cells remain viable 24 h after encapsulation, and further studies are warranted to define the viability of cells freed from the microcapsules, by approaching their ability to proliferate and differentiate.…”
Section: Discussionmentioning
confidence: 99%
“…The precision of FDM is influenced by various factors, such as temperature and large scale of release nozzle, which is hard to satisfy the printing precision of microneedles [17]. Similar limitations exist in SLA and SLS, while the minimum feature size of SLS and SLA is larger than 100 microns [18]. Moreover, SLS requires high power supply and printing temperature, which would raise the cost of fabrication.…”
Section: Of 11mentioning
confidence: 99%
“…However, these methods are costly, not readily available and therefore not convenient for in-house microneedle manufacture by most researchers interested in microneedle applications. Various low-cost vat photopolymerization-based AM methods have also been explored for MNA fabrication, including projection-based direct light processing (DLP) 4144 and scanning-based stereolithography (SLA) 45,46 . In DLP, a digital mirror projects each cross-sectional layer which cures the photopolymer and this process is repeated as the part is built in a layer-by-layer approach.…”
Section: Introductionmentioning
confidence: 99%